1992
DOI: 10.1200/jco.1992.10.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting treatment responsiveness and prognosis in node-negative breast cancer. The International (Ludwig) Breast Cancer Study Group.

Abstract: Hormone receptor status and tumor grade are important factors for predicting responsiveness to perioperative chemotherapy in node-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
2
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 29 publications
4
34
2
3
Order By: Relevance
“…Earlier analyses of the entire IBCSG Trial V data set of 1275 LN negative patients at 5 years of median follow-up were able to detect significant improvements in DFS for patients who received the PeCT regimen, especially among those with BRG 2 and 3 tumors. 3 The difference in conclusions between the earlier publication and our analysis appears to be due to the inclusion of late term effects of PeCT. In particular, those patients with rapidly proliferating or Grade 3 tumors, for whom special benefit from chemotherapy has been suggested, did not demonstrate a significantly improved DFS or OS with a single cycle of combination treatment at a median of 12 years of follow-up.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Earlier analyses of the entire IBCSG Trial V data set of 1275 LN negative patients at 5 years of median follow-up were able to detect significant improvements in DFS for patients who received the PeCT regimen, especially among those with BRG 2 and 3 tumors. 3 The difference in conclusions between the earlier publication and our analysis appears to be due to the inclusion of late term effects of PeCT. In particular, those patients with rapidly proliferating or Grade 3 tumors, for whom special benefit from chemotherapy has been suggested, did not demonstrate a significantly improved DFS or OS with a single cycle of combination treatment at a median of 12 years of follow-up.…”
Section: Discussioncontrasting
confidence: 53%
“…The trial and the clinical results have been described in detail elsewhere. 3,9,10 In this study, the two treatment arms that received prolonged chemotherapy (conventionally timed with or without perioperative chemotherapy) were combined because the prognoses for these two groups were similar.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, tumour cell emboli in lymph and blood vessels are considered to be the morphological correlates of BC metastasising to loco-regional lymph nodes (LNs) and distant haematogenous sites, respectively. The presence of lymphovascular invasion indeed has been correlated to the presence of LN metastases and to poor prognosis in patients with BC (Sampat et al, 1977;Nealon et al, 1979Nealon et al, , 1981Dawson et al, 1982Dawson et al, , 1986Weigand et al, 1982;Bettelheim et al, 1984;Berger et al, 1988;Rosen et al, 1989Rosen et al, , 1991Lee et al, 1990;Clayton, 1991;Clemente et al, 1992;Neville et al, 1992;Fisher et al, 1993a, b;Lauria et al, 1995). Recently, interest in (lympho)vascular invasion has been increased owing to addition of peritumoural (lympho)vascular invasion to the St Gallen criteria for selection of adjuvant systemic treatment in operable BC (Goldhirsch et al, 2005).…”
mentioning
confidence: 99%
“…Although few studies have reported controversial roles for lymphovascular invasion as a prognostic factor (3, 14, 21), a great number of studies have confirmed the important role lymphovascular invasion plays in survival prognosis of breast cancer patients (Neville et al, 1992;Lauria et al, 1995;Camp et al, 2000;Voogd, 2001;Woo et al, 2002;Kuru et al, 2003;Sebastian et al, 2004;Pauline et al, 2005;Ashwini et al, 2008). The results of the present study are in line with those of the most recent studies and show the important role lymphovascular invasion plays as an independent prognostic risk factor in both lymph node negative and positive patients.…”
Section: Discussionmentioning
confidence: 98%